The gender tax: Ensuring gender integration in research - Lannerstad, Mats (International Livestock Research Institute, 2016)
In 2015, a considerable amount of money was set aside for CGIAR projects that were not gender-focused so they could develop proposals and apply for funds to integrate gender in their research. This was a clever way to move money from generic purposes to specific activities. If people have to integrate gender in their work, they often do not know what to do. This internal call for proposals forced them to think precisely about what to do; in this they were supported by gender scientists. The outcomes are reflected in this book, but more importantly, scientists have developed new knowledge and have been inspired to integrate gender in future proposals. They can now help their fellow scientists to work on gender. Interview with Mats Lannerstad (ILRI) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684